Estrategias significativas para resolver situaciones multiplicativas - Rodriguez Saavedra, Juliana (2021)
This research work entitled "Meaningful strategies to solve multiplicative situations" was applied in the field of Mathematics for the fourth grade of Primary Education. The Introduction is aimed at promoting in students attitudes of interest to solve multiplicative problem situations, using various strategies and being able to search, organize, systematize and analyze information, understand the world around them, function in it, take relevant decisions and solve problems in different situations. In the second part, it is developed the Theoretical Basis where the conceptual definitions of the four significant multiplication strategies based on the Problem Solving Approach, in order to explain what is stated in the present work, in a simple way and with a scientific theoretical basis to support it. Finally, the third part is devoted to the Pedagogical Support, the fundamentals of the Mathematics Field according to the new Curriculum framework, considering my pedagogical experience in the graduation profile that the student must achieve at the end of the Regular Basic Education and the problem solving approach that guides this field, besides the pedagogical and didactic processes of the field.